Chemoprevention of Breast Cancer by Dietary Polyphenols - Maria-Magdalena Mocanu; Péter Nagy; János Szöllősi (Molecules, 2015)
The review will discuss in detail the effects of polyphenols on breast cancer, including both the advantages and disadvantages of the applications of these natural compounds. First, we focus on the characterization of the main classes of polyphenols and then on in vitro and in vivo experiments carried out in breast cancer models. Since the therapeutic effects of the administration of a single type of polyphenol might be limited because of the reduced bioavailability of these drugs, investigations on combination of several polyphenols or polyphenols with conventional therapy will also be discussed. In addition, we present recent data focusing on clinical trials with polyphenols and new approaches with nanoparticles in breast cancer. Besides the clinical and translational findings this review systematically summarizes our current knowledge about the molecular mechanisms of anti-cancer effects of polyphenols, which are related to apoptosis, cell cycle regulation, plasma membrane receptors, signaling pathways and epigenetic mechanisms. At the same time the effects of polyphenols on primary tumor, metastasis and angiogenesis in breast cancer are discussed. The increasing enthusiasm regarding the combination of polyphenols and conventional therapy in breast cancer might lead to additional efforts to motivate further research in this field.